Major John Richardson: Canadian Patriot and Literary Nationalist - Finlayson, Alan (Ontario History, 2019)
Major John Richardson has been recognized as “the father” of Canadian literature as well an early historian of the War of 1812 but his writings, rich in detail and highly autobiographical, have not been sufficiently appreciated by historians as valuable historical source materials. Yet they provide accurate portrayals of contemporary Upper Canadian perceptions and attitudes similar to those found in the writings of the more popular Brock, Strachan, Mackenzie, Robinson, Baldwin, and Ryerson. Richardson also deserves greater recognition for his role as a Canadian patriot and nationalist. Despite living abroad, he consistently proclaimed himself “a Canadian”, and hoped, through his works, to “infuse” into the Canadian community “a spirit of National literature.” His writings reflect the pride and emerging Canadian national spirit and as such merit greater attention by historians.